Ulnar nerve at the elbow - normative nerve conduction study - Ehler Edvard; Ridzoň Petr; Urban Pavel; Mazanec Radim; Nakládalová Marie; Procházka Bohumír; Matulová Hana; Latta Ján; Otruba Pavel (Biomed Central, Ltd., 2013)
Introduction: A goal of our work was to perform nerve conduction studies (NCSs) of the ulnar nerve focused on the nerve conduction across the elbow on a sufficiently large cohort of healthy subjects in order to generate reliable reference data.Methods: We examined the ulnar nerve in a position with the elbow flexion of 90o from horizontal. Motor response was recorded from the abductor digiti minimi muscle (ADM) and the first dorsal interosseous muscle (FDI).Results: In our sample of 227 healthy volunteers we have examined 380 upper arms with the following results: amplitude (Amp)-CMAP(wrist) for ADM 9.6 ? 2.3 mV, MNCV at the forearm 60.4 ? 5.2 m/s, MNCV across the elbow 57.1 ? 5.9 m/s.Discussion: Our study showed that motor NCSs of the ulnar nerve above elbow (AE) and below elbow (BE) in a sufficiently large cohort using methodology recommended by AANEM gave results well comparable for registration from FDI and ADM.
Loketní nerv v lokti - normativní nerv vedení studie
Keywords: ulnar nerve; nerve conduction studies; semiflexion in elbow; methodology; normative values; loketní nerv; neurografie; semiflexe v lokti; metodologie; normální hodnoty